AKUNTABILITAS PENGELOLAAN DANA DESA - Selva Temalagi; Fanny Monica Anakotta (Program Studi Akuntansi PSDKU Universitas Pattimura, 2021)
The purpose of this study was to empirically examine the effect of financial statement presentation,financial statement accessibility, and internal control system on village fund managementaccountability. The results of the research are expected to be able to contribute to: 1) VillageGovernment, providing an understanding related to the rules in managing village finances andaccountability of village funds.The research population is village officials in Central Maluku district. The sample is the villagehead, village secretary, village treasurer and section head in 22 villages in Central Maluku districtlocated on Ambon Island. The sampling technique in this research uses the Purposive SamplingTechnique. The type of data is primary data collected through a questionnaire method distributedto 110 respondents, data that can be processed by a number of respondents.Data analysis method using SEM-PLS. The results of the study show: 1) the presentation offinancial statements has a positive effect on the accountability of village fund management, 2) theaccessibility of financial reports has a positive effect on the accountability of village fundmanagement, 3) the internal control system has a positive effect on the accountability of villagefund management.